2018
DOI: 10.1101/481713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular requirements for transition from lateral to end-on microtubule binding and dynamic coupling

Abstract: Abbreviations: MAP -microtubule associated protein, MT -microtubule, MSD -mean squared displacement, TIRF -total internal reflection fluorescence. ABSTRACTAccurate chromosome segregation relies on microtubule end conversion, the ill-understood ability of kinetochores to transit from lateral microtubule attachment to durable association with dynamic microtubule plus-ends. The molecular requirements for this conversion and the underlying biophysical mechanisms are ill-understood. We reconstituted end conversion … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…When incubated with stabilized microtubules in vitro, the oligomers interacted with the microtubule walls (Figure 3C, D). Using immunofluorescence, we confirmed that the microtubule-bound oligomers had copurified with the NDC80 complex (Supplementary Figure 2C), which likely mediated their interaction with microtubules 2,39,40 . By contrast, GFP oligomers isolated from mitotic HeLa cells did not bind microtubules (Figure 3C, D), indicating that microtubulebinding is specific to CENP-T 1-242 oligomers.…”
Section: Cenp-t-based Kinetochore-like Particles Are Functionally Sim...mentioning
confidence: 72%
“…When incubated with stabilized microtubules in vitro, the oligomers interacted with the microtubule walls (Figure 3C, D). Using immunofluorescence, we confirmed that the microtubule-bound oligomers had copurified with the NDC80 complex (Supplementary Figure 2C), which likely mediated their interaction with microtubules 2,39,40 . By contrast, GFP oligomers isolated from mitotic HeLa cells did not bind microtubules (Figure 3C, D), indicating that microtubulebinding is specific to CENP-T 1-242 oligomers.…”
Section: Cenp-t-based Kinetochore-like Particles Are Functionally Sim...mentioning
confidence: 72%